2007
DOI: 10.1016/s0929-6646(08)60022-4
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Dexamethasone Pretreatment Reduces Fentanyl-induced Cough

Abstract: DEX (10 mg, IV) 5 minutes prior to fentanyl injection reduces the incidence of FIC and can be an ideal premedicant for general anesthesia induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Many factors have been associated with fentanyl-induced cough, such as drug dosage and concentration, order of drug administration, intravenous injection rate and site [8], individual physical condition, age, sex, weight, disease history, smoking, and family genetics. A number of techniques have been applied to reduce the incidence of fentanylinduced cough, including the use of betamethasone (8.3 vs. 35%), dexamethasone (6.3 vs. 21.3%) [9], ephedrine (21 vs. 65%) [10], lidocaine (13.1%) [11], ketamine (7.2 vs. 21.6%) [12], and propofol (6.7%) [13], a change the order of administering the drugs, the speed of fentanyl administration, and fentanyl concentration. The use of the drugs in these earlier studies was unable to completely prevent fentanyl-induced cough, and some of them are very limited in terms of their clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors have been associated with fentanyl-induced cough, such as drug dosage and concentration, order of drug administration, intravenous injection rate and site [8], individual physical condition, age, sex, weight, disease history, smoking, and family genetics. A number of techniques have been applied to reduce the incidence of fentanylinduced cough, including the use of betamethasone (8.3 vs. 35%), dexamethasone (6.3 vs. 21.3%) [9], ephedrine (21 vs. 65%) [10], lidocaine (13.1%) [11], ketamine (7.2 vs. 21.6%) [12], and propofol (6.7%) [13], a change the order of administering the drugs, the speed of fentanyl administration, and fentanyl concentration. The use of the drugs in these earlier studies was unable to completely prevent fentanyl-induced cough, and some of them are very limited in terms of their clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Effectively reducing fentanyl-induced cough response from 28% to 6% after aerosol inhalation of salbutamol (a selective β 2 -adrenergic bronchodilator) further supports the mechanism that fentanyl induces cough via its bronchoconstriction effect (5). In addition, opioid-induced histamine release (14) and muscle rigidity leading to sudden adduction of the vocal cords or supraglottic obstruction (15) are plausible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort study of 1311 adult patients, these authors reported that increasing age, cigarette smoking, prior epidural injection of lidocaine or a priming dose of vecuronium were associated with a decreased risk of fentanyl-induced cough (4, 15, 18). Lin et al found that only light smoking, not heavy smoking could decrease the frequency of fentanyl-induced cough, but the association between age and incidence of cough was not observed in their study (7, 11, 19). In Tang and his colleagues' study, the incidence of cough was 80%.…”
Section: Discussionmentioning
confidence: 69%
“…Former reports have demonstrated that a fentanyl-induced cough can be reduced with pretreatment of certain drugs (4-9). Strategies to decrease the occurrence of a reflex cough following an intravenous bolus of fentanyl include techniques to prolong injection time or the use of terbutaline, clonidine, dexamethasone and lidocaine (1, 4, 7, 8, 10, 11) however, these approaches are not uniformly effective. All of these medications have bronchorelaxant effects on the airway's smooth muscle (4, 5, 12).…”
Section: Introductionmentioning
confidence: 99%